Development and investigation of bileaflet heart valve prostheses - Ramesh Veerappan (2008)
Artificial heart valves are in use the last four decades. They seem to be gaining ever increasing popularity though they are prone to have problems such as thrombosis and haemolysis. Of the mechanical heart valves available, the bileaflet valves exhibit superior haemodynamic characteristics over the rest. Commercially available bileaflet valves at times malfunction due to the improper valve closure caused by the hindering micro thrombus caught in the recess of the pivot structure. This may lead to insufficiency or even to the extent of catastrophic valve malfunction.